2006
DOI: 10.1007/s11095-005-8716-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Milk/Plasma Drug Concentration (M/P) Ratio Using Support Vector Machine (SVM) Method

Abstract: The classification accuracy of training set and test set for SVM was 90.63 and 90.00%, respectively. The total accuracy for SVM was 90.48%, which was higher than that of LDA (77.78%). Comparison of the two methods shows that the performance of SVM was better than that of LDA, which implies that the SVM method is an effective tool in evaluating the risk of drugs when experimental M/P ratios have not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…11,13,39,40 SVC was originally developed by Vapnik and coworkers 11 and it has shown promising capability for solving a number of biological classification problems. 14,[16][17][18][19][20][23][24][25][26][27][28][29] SVC is based on the structure risk minimization (SRM) principle from statistical learning theory. 11 For linearly separable cases, SVC performs classification tasks by constructing a hyperplane in a multidimensional space to separate two different classes of feature vectors with a maximum margin.…”
Section: Svc Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,39,40 SVC was originally developed by Vapnik and coworkers 11 and it has shown promising capability for solving a number of biological classification problems. 14,[16][17][18][19][20][23][24][25][26][27][28][29] SVC is based on the structure risk minimization (SRM) principle from statistical learning theory. 11 For linearly separable cases, SVC performs classification tasks by constructing a hyperplane in a multidimensional space to separate two different classes of feature vectors with a maximum margin.…”
Section: Svc Algorithmmentioning
confidence: 99%
“…On the other hand, it has been reported that some ML methods such as support vector classification (SVC) have consistently shown excellent performance for the prediction of Pglycoprotein substrates, 16 tetrahymena pyriformis toxicity chemicals, 20 ADME property, 23 milk/plasma drug concentration (M/P) ratio, 24 estrogen receptor-beta ligands, 25 cytochrome inhibitors, 26 factor Xa inhibitors, 27 anti-HIV nucleoside derivatives, 28 and human pregnane X receptor activation. 29 Therefore, it is desirable to test the usefulness of SVC and other ML methods as potential tools for the prediction of antibacterial compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Katritzky et al [7] investigated the prediction of M/P ratios for a set of 115 drugs using multiple linear regression. Zhao et al [20] used a support vector machine, SVM, method to analyze M/P ratios for 126 drugs. The only statistic they gave was an 'accuracy' of 90.48 %.…”
Section: Ei ð%þ ¼ 100 â ðM=pþ â A=infantdrugclearance ð1þmentioning
confidence: 99%
“…[20][21][22] The advantage of including such a wide range of molecules for development of quantitative models is that the models encompass a wide range of applicability domain and hence can be successfully utilized for prediction of a variety of untested molecules. The data were assigned as high risk (H) (M/P > 1) and low risk (L) (M/P < 1) drugs as proposed by Malone et al [25] for classification based QSTR model.…”
Section: Datasetmentioning
confidence: 99%
“…Then, research on its theoretical and application aspects thrived. It has been applied in a wide range of problems, including text categorization (de Vel et al, 2001;Kim et al, 2001), image classification and object detection (Ben-Yacoub et al, 1999;Karlsen et al, 2000), flood stage forecasting (Liong and Sivapragasam, 2002), microarray gene expression data analysis (Brown et al, 2000), drug design (Zhao et al, 2006a(Zhao et al, , 2006b, protein solvent accessibility prediction (Yuan et al, 2002), and protein fold prediction (Ding and Dubchak, 2001;Hua and Sun, 2001). Many studies have demonstrated that SVM was consistently superior to other supervised learning methods (Brown et al, 2000;Burbidge et al, 2001;Cai et al, 2003).…”
mentioning
confidence: 99%